Study on Design and Implementation of E-Commerce Web Application - V. Vinitha Stephie; M. Lakshmi (Novel Perspectives of Engineering Research Vol. 2, 2021)
The primary focus of this paper work is about the design of Web portal for the trading and welfare for pets. A “usability subculture” has evolved as a result of emerging web technologies. The user centered design will become more important in an increasingly competitive market. Because of this application the users can make an ease approach into Veterinary Science, clubs, buying and selling of pets and its accessories. By viewing this site, one can make clear decision while buying a new pet initially. Further one can get to know information about the breed and its life cycle, in regard with its nature, habitant, food culture and purpose. The people who are fond of animals can opt themselves as a social reformer. A user can also enroll themselves as a community member and have a full access towards its responsibilities. In additional, anyone can get to know about nearby localities anywhere related to pets. The pretty advantage of this site is that it allows the user to experience the usability before they could put up their mind to buy. Thus the e-commerce website is displayed as an electronic storefront and the web user interface servers as an electronic clerk and electronic catalogue for direct sales.